Ecological and biological features of endemic species of Colchian bladder nut (Staphylea colchica Stev.) under the conditions of ASU botanic garden - Lihota O. S., Fomina N. S. (Academic community of students, 2016)
The results of the study of the biological and physiological characteristics staphylea colchica growing in a botanical garden of the Adygeya State University. Phenological observations were carried out, which allowed to determine the age of transition staphylea colchica in generative state. Anatomic features of the stem structure. Studied some indicators of water leaves staphylea colchica regime (total water content and water-holding capacity).
Keywords: адаптация; фенология; показатели водного режима; adaptation; клекачка колхидская; эндемичные; анатомическое строение стебля; rare and endangered species; phenology; the anatomical structure of the stem; staphylea colchica endemic; water regime indicators; редкие виды; исчезающие виды